The behavioural turn in consumer policy: Perspectives and clarifications - Francesco Bogliacino; Cristiano Codagnone; Giuseppe Alessandro Veltri (Intereconomics, 2015)
This article critically discusses the potential of the new behavioural turn in consumer policy. It focuses on methodological and normative aspects, which are not suffi ciently discussed in the policy domain, in particular on the lessons that can be learned from randomised control trials and the normative side of the intervention. Some implications for consumer policies are drawn, proposing a new taxonomy of interventions.
Keywords: 330; Verbraucherpolitik; Kritik; Verhaltensökonomik; Neoklassische Theorie; EU-Staaten